Restorative Circles as a Means of Proactive Student Self-Assessment: Integrating the Wellbeing Agenda into the Junior Cycle English Classroom - Gough, Karl (STER, 2024)
The aim of this article is to investigate if using ‘Restorative Circles’ in the Junior Cycle English classroom can foster the conditions needed to promote a sense of belonging at school. It seeks to address how a strategy associated with Restorative Practices can allow teachers and students to communicate in ways which encourage both parties to assess their behaviour and learning in the classroom. Such is key to the fostering of positive interpersonal relationships between teachers and students and is integral to the conditions needed to strengthen the sense of belonging at school for students. This brings us to the research question: ‘How can Restorative Circles support the development of well-being in the English classroom? The subject of English holds great potential in this as many of its curricular aims are centred on engendering learning dispositions which can enable students to become critical and compassionate learners. This is a synopsis of a longer piece of research from a professional dissertation which presents evidence which finds that teachers also occupy an important role in fostering the learning dispositions of students at school. It is imperative then that they remain aware of their role in mediating the school-going experience for students as well as cognisant of their responsibility to teach them in class. In preparing children and young people with what they need to create a better world for the future, teachers must actively seek out new ways of facilitating positive relationships with and among their students at school. In doing so, the school can promote a practice of teaching that fosters the well-being of its students.
Keywords: Restorative Practice; Restorative Circles; Student Wellbeing; Junior Cycle; English